Newborn Umbilical Cord Care in Parakou in 2013: Practices and Risks - AGOSSOU, JOSEPH; D'ALMEIDA, Marcelline; ADEDEMY, JULIEN DIDIER; NOUDAMADJO, Alphonse; GOUNOU N'GOBI, Doué Yasmine; AYIVI, BLAISE (My University, 2016)
Objective: The objective was to study umbilical care practices and risks in Parakou (North Benin). Patients and method: It was a cross-sectional and descriptive study carried out within a commu- nity from June 1 to August 31, 2013. It focused on all the infants born at the maternity of Parakou Health Center and their mothers. Results: Two hundred and ten newborns were included i.e. 101 boys and 109 girls. In 80.9% of cases, inappropriate substances had been applied to umbilical cord. Umbilical cord care quality was adjudged as poor, acceptable and good in 58.6%, 31.9% and 9.5% of cases respectively. A bacterial umbilical infection had been noted in 59.5% of newborns. Only 4.8% had sterile umbilical wound. The commonest bacteria were: Staphylococcus aureus (58.1%), Staphylococcus saprophiticus (53.3%), Escherichia coli (44.8%) and Pseudomonas aeruginosa (14.3%). The factors associated with umbilical infection were: low educational status of mother (p = 0.026), low-income occupation of mother (p = 0.021), customary practices to accelerate umbilical cord fall off (p = 0.007), short time to cord falling off lower than 6 days (p = 0.015). Conclusion: Umbilical cord care involves high risk for bacterial infection in our context. Strong actions must be taken within the community in order to reduce that risk.
Keywords: Umbilical Care Practices; Risks; Newborn; Parakou; Benin